2014
DOI: 10.1371/journal.pone.0112405
|View full text |Cite
|
Sign up to set email alerts
|

Weight-Bearing MR Imaging as an Option in the Study of Gravitational Effects on the Vocal Tract of Untrained Subjects in Singing Phonation

Abstract: Magnetic Resonance Imaging (MRI) of subjects in a supine position can be used to evaluate the configuration of the vocal tract during phonation. However, studies of speech phonation have shown that gravity can affect vocal tract shape and bias measurements. This is one of the reasons that MRI studies of singing phonation have used professionally trained singers as subjects, because they are generally considered to be less affected by the supine body position and environmental distractions. A study of untrained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
15

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 22 publications
0
27
0
15
Order By: Relevance
“…Upright scanners can potentially overcome these problems, and there have been a few studies that demonstrate their utility in RT-MRI of speech research. [90][91][92] The use of iterative constrained reconstruction algorithms have been shown to improve the SNR from low field simulated measurements, and these hold great potential in future use of upright low field scanners for RT-MRI of the upper airway. 93 The clinical role of RT-MRI in the assessment of abnormal vocal tract and upper airway dynamics has not yet been determined, and remains an exciting area for investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Upright scanners can potentially overcome these problems, and there have been a few studies that demonstrate their utility in RT-MRI of speech research. [90][91][92] The use of iterative constrained reconstruction algorithms have been shown to improve the SNR from low field simulated measurements, and these hold great potential in future use of upright low field scanners for RT-MRI of the upper airway. 93 The clinical role of RT-MRI in the assessment of abnormal vocal tract and upper airway dynamics has not yet been determined, and remains an exciting area for investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This is the case for high-pitched singing or vowels with a wide mouth opening like the vowel /a/. Another focus was set on the effect of the body position during phonation as MRI-imaging is commonly performed in supine position [23,24]. The reports showed that the effect of the supine position is statistically insignificant for different registers of professional tenors, whereas 5 out of 10 untrained singers phonated statistically significantly different being unable to completely compensate the different direction of the gravitation force in the supine position.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most consistent observations is that the pharyngeal (nasopharyngeal and/or oropharyngeal) cavity is smaller in the supine as opposed to the upright position during speech, as determined from APh (Jan et al, 1994), computed tomography (CT; Sutthiprapaporn et al, 2008), MRI (Engwall, 2006;Kitamura et al, 2005;Traser et al, 2014), ultrasound (Stone et al, 2007;Wrench et al, 2011), x-ray microbeam (Tiede et al, 2000), and videofluoroscopy (Bae et al, 2014). This effect can be explained by gravity pulling the tongue root posteriorly when the subject is in the supine position, thereby reducing the size of the pharynx.…”
mentioning
confidence: 99%
“…In an electromyographic study, Moon and Canady (1995) observed a reduced level of muscle activity in the levator veli palatine for phonation in the supine as opposed to the upright position. In a MRI study of untrained singers, Traser et al (2014) observed elongation of the uvula in the upright position.…”
mentioning
confidence: 99%